Hematoma - A Complication of Posterior Superior Alveolar Nerve Block - Kunwarjeet Singh; Nidhi Gupta; Sidarth Sharma (Journal of Dental Problems and Solutions - Peertechz Publications, 2015)
The administration of anesthesia in dentistry is necessary to prevent pain in specific area of the oral cavity which is accomplished by blocking the branches of the trigeminal nerve. Posterior superior alveolar nerve block is most commonly used for the surgical procedures, extraction or root canal treatment of the maxillary molars (with possible exception of mesiobuccal root of maxillary first molar) and buccal soft tissues. The injection of local anesthesia is usually safe but a rare complication of extraoral hematoma formation in the mandibular lower buccal region might occur due to the insertion of the needle to far posteriorly into the pterygoid plexus of veins, maxillary artery - posterior superior alveolar artery and the facial artery which is esthetically unpleasant to the patient and quite embarrassing for the dentist.This case report describe the complication of posterior superior alveolar nerve block and its management.